FILSAFAT SEBAGAI PREPARATIO EVANGELICA: Selayang Pandang Peranan Filsafat Hellenisme Pada Awal Pewartaan Kekristenan - Tinambunan, Laurentius (UNIKA Santo Thomas, 2008)
The intertestamental period is the time that elapsed from the last writings of the Old Testament to the early formulation of Christian Theology (New Testament). The period was marked by a powerful cultural heritage called Hellenism that influenced also the Jews community. One of the most notable effects that Hellenism was to have upon the Jews was the translation of the Hebrew Old Testament into the Greek language (the Septuagint LXX). Philosophy, as the teaching of how to achieve happiness, is one of the element which spread across the Mediteranean during the long period of hellenisation. There is no doubt that the Hellenistic philosophy played a significant role in Jews community before and during the New Testament era. This fact rises a question about the relation of the Hellenistic Philosophy and the formulation of early Christian Theology. This paper tries to show several Hellenistic philosophical thoughts which, in certain sense, resound in the New Testament.